Brain Activity During Paired and Individual Mindfulness Meditation: A Controlled EEG Study. - Engelbregt, Hessel; de Grauw, Sietske; Baas, Hugo F. Alderse; Deijen, Jan Berend (International Journal of Transpersonal Studies, 2021)
Objective: In this study, we evaluated brain electroencephalographic (EEG) activity in healthy participants during the performance of paired and individual mindfulness meditation (MM). We hypothesized that EEG activity is differentially affected by meditation in pairs compared to individual meditation. Methods: A total of 20 healthy female university students (mean age 19.54 years, SD =1.53) with no prior experience in MM participated in this study. All participants had to perform a 5-minute MM task together and individually while the other participant was in rest or performing a concentration task (control condition). To exclude social interaction as main factor, participants were separated from their research partner by an opaque screen while instructions were given through headphones. Brain electroencephalographic (EEG) activity from each individual student was measured during all conditions. Results: The main findings indicate that left-frontal alpha and theta spectral EEG power was significantly higher during the paired MM condition compared to individual MM and control condition. Conclusions: This controlled MM study demonstrates differences in brain activity between practicing mindfulness in pairs compared to practicing it individually. We conclude that the increased alpha and theta EEG power during paired MM may be associated with social facilitation or the activation of "theory of mind." The results invite further reflection on interpersonal communication and mindfulness.